Development of a DC-DC converter for DC bus voltage control of series connected device - Monteiro, T. C.; Galassi, M.; Terrazas, T. M. [UNESP]; Marafão, F. P. [UNESP]; Matakas, L.; Komatsu, W. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
The purpose of this work is to study voltage control and energy balance of a split DC bus topology within a power electronics equipment connected to the AC mains, such as UPS systems, wind power generators, active filters and FACTS devices. A typical configuration in such equipment has two mains connected converters sharing a common DC bus, one series connected and the other parallel connected. The DC bus is usually composed by a battery or a capacitor bank. In the proposed topology, the DC bus is divided in two sides, interconnected with a buck-boost converter, which controls power flow and DC voltage on both sides. © 2009 IEEE.
Keywords: Buck-boost converter; DC bus voltage control; Buck boost converter; Bus topology; Capacitor bank; Common DC bus; DC voltage; DC-bus voltages; Facts devices; Parallel-connected; Power flows; UPS systems; Wind power generators; Active filters; Capacitors; Electric converters; Electric potential; Topology; Voltage control; Voltage regulators; Wind power; Power electronics